2020
DOI: 10.7717/peerj.8565
|View full text |Cite
|
Sign up to set email alerts
|

Embodied time and the out-of-body experience of the self

Abstract: Using an out-of-body paradigm, the present study provided further empirical evidence for the theory of embodied time by suggesting that the body-self plays a key role in time judgments. Looking through virtual reality glasses, the participants saw the arm of a mannequin instead of their own arm. They had to judge the duration of the interval between two (perceived) touches applied to the mannequin’s body after a series of strokes had been viewed being made to the mannequin and tactile strokes had been administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 45 publications
0
8
1
Order By: Relevance
“…Along this line of reasoning, some theorists have recently proposed an embodied account of time perception (Droit‐Volet, Fayolle, Lamotte, & Gil, 2013, 2020; Wittmann, 2014), which differs from other existing models (e.g., Gibbon, Church, & Meck, 1984; Treisman, Faulkner, Naish, & Brogan, 1990; Zakay & Block, 1997) as it claims that motor simulations and bodily states play a critical role in time judgments. In more detail, it has been argued that the conscious representation of time descends from a temporal integration of bodily feelings over time (e.g., Craig, 2009; Wackermann, Meissner, Tankersley, & Wittmann, 2014; Wittmann, 2013, 2014), including those associated with self‐generated movements (Fernandes & Garcia‐Marques, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Along this line of reasoning, some theorists have recently proposed an embodied account of time perception (Droit‐Volet, Fayolle, Lamotte, & Gil, 2013, 2020; Wittmann, 2014), which differs from other existing models (e.g., Gibbon, Church, & Meck, 1984; Treisman, Faulkner, Naish, & Brogan, 1990; Zakay & Block, 1997) as it claims that motor simulations and bodily states play a critical role in time judgments. In more detail, it has been argued that the conscious representation of time descends from a temporal integration of bodily feelings over time (e.g., Craig, 2009; Wackermann, Meissner, Tankersley, & Wittmann, 2014; Wittmann, 2013, 2014), including those associated with self‐generated movements (Fernandes & Garcia‐Marques, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A high level of sensitivity to affective stimuli and weaker cognitive functionality would indicate that self-regulation is more affect dominant than cognitive dominant within the bidirectional relationship. This sensitivity may also influence the differences in temporal processing associated with ADHD, as research into models of time processing or the “internal clock” highlight the dependence of time awareness on attentional executive control processes (Droit-Volet et al, 2018) and the premotor cortex (Droit-Volet, Monceau, et al, 2020), the influence of dopaminergic activation of cortico-striatal circuits including attention and working memory (Toplak et al, 2006) and the effect of emotion and arousal on the magnitude of time distortions (Droit-Volet, 2018; Droit-Volet, El-Azhari, et al, 2020; Droit-Volet et al, 2018; Vasile, 2015). Research also shows that individuals with ADHD experience cognitive domain-dependent neuro-functional impairments in different neural networks depending on the cognitive context (Dibbets et al, 2010; Hart et al, 2012).…”
Section: Sdt Etiology Of Adhdmentioning
confidence: 99%
“…The impacts of the altered neural processing on embodied time (Droit-Volet, Monceau, et al, 2020) also have a developmentally negative impact on perceived competence. More affect-dominant self-regulation combined with an altered perception of embodied time may result in reduced sensitivity to longer durations but a higher response to shorter durations, as the experience of time fluctuates according to arousal and affect (Droit-Volet et al, 2013).…”
Section: Psychopathologymentioning
confidence: 99%
“…Moreover, Bergouignan, Nyberg, and Ehrsson found reduced hippocampal activity during retrieval in the out-of-body condition. Furthermore, in a recent re-analysis of their data, the authors found that disrupting sense of self in space also reduces the ability to remember events from a eld perspective (Bergouignan et al, 2014(Bergouignan et al, , 2021 [43,68] . Together, these ndings suggest that multisensory processes underlying the sense of self and egocentric mapping of space in the posterior parietal regions are conveyed to the hippocampus in order to build a coherent representation of the manifold dimensions of experience centered around the bodily-self.…”
Section: The Impact Of Synchronous Vs Asynchronous Conditionmentioning
confidence: 99%